Debt and Crisis in Latin America : the Supply Side of the Story. - Devlin, Robert (Princeton legacy library., 2014)
Examining the causes of the acute Latin American debt crisis that began in mid-1982, North American analysts have typically focused on deficiencies in the debtor countries' economic policies and on shocks from the world economy. Much less emphasis has been placed on the role of the region's principal creditors--private banks--in the development of the crisis. Robert Devlin rounds out the story of Latin America's debt problem by demonstrating that the banks were an endogenous source of instability in the region's debt cycle, as they overexpanded on the upside and overcontracted on the downsi.